1999
DOI: 10.1677/joe.0.1620207
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and isoform-selective activation of protein kinase C in insulin-resistant obese Zucker rats - effects of feeding

Abstract: The mechanisms of insulin resistance in the obese Zucker rat have not been clearly established but increased diacylglycerol-protein kinase C (DAG-PKC) signalling has been associated with decreased glucose utilisation in states of insulin resistance and non-insulin-dependent diabetes mellitus. The purpose of this study was to characterise tissue-and isoform-selective differences in DAG-PKC signalling in insulin-sensitive tissues from obese Zucker rats, and to assess the effects of feeding on DAG-PKC pathways. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 31 publications
4
80
0
Order By: Relevance
“…PKC redistribution was reversed upon treatment with the insulin sensitizer rosiglitazone (12). Similar alterations in nPKC isoforms were also observed in genetic models of obesity and diabetes (13,14). In more acute models of insulin resistance, PKC translocation was also observed after 5-h lipid infusion (15), whereas 1-or 4-day infusion of glucose, which increased muscle lipid content, promoted activation of PKCε (16).…”
Section: Pkc and Insulin Resistancementioning
confidence: 68%
“…PKC redistribution was reversed upon treatment with the insulin sensitizer rosiglitazone (12). Similar alterations in nPKC isoforms were also observed in genetic models of obesity and diabetes (13,14). In more acute models of insulin resistance, PKC translocation was also observed after 5-h lipid infusion (15), whereas 1-or 4-day infusion of glucose, which increased muscle lipid content, promoted activation of PKCε (16).…”
Section: Pkc and Insulin Resistancementioning
confidence: 68%
“…Membrane translocation for the different PKC isoforms (PKC-α, -β, -ε, -δ, -θ, -η, -λ, -ι, -ζ, and -γ) was performed as described previously (47). Both membrane and cytosol proteins were detected on the same film with enhanced chemiluminescense at the same exposure time.…”
Section: Methodsmentioning
confidence: 99%
“…Among the serine kinases implicated in Ser phosphorylation of the IR and the IRSs, protein kinase C (PKC) is one candidate with potential pathophysiological relevance. Numerous studies have linked excessive PKC activity to diminished insulin sensitivity, especially to that occurring together with increased lipid availability (Considine et al 1995, Qu et al 1999, Itani et al 2000. We have previously reported that IR Ser994 is an in vitro phosphorylation target for PKC (Coba et al 2003).…”
Section: Introductionmentioning
confidence: 95%